IDEOLOGY AND REPRESENTATION OF ENVIRONMENTAL AMANAH ADVICE IN THE MALAY TEACHING BOOK BY TENAS EFFENDY - Nurzuha; Agustina (SOSIOEDUKASI, 2026)
This study aims to analyze the ideology contained in the Petuah Amanah Alam Lingkungan in Tunjuk Ajar Melayu by Tenas Effendy, as well as to explore how the representation of this ideology can be applied in the modern context, particularly in environmental preservation. The research utilizes a qualitative approach with the Critical Hermeneutic method. Data is obtained through an analysis of the Petuah Amanah Alam Lingkungan text, which is examined using the ideologies of cosmocentricism and environmental ethics. The findings show that in Tunjuk Ajar Melayu, there is a cosmocentric worldview that positions nature as a sacred entity that must be preserved. Nature is seen as a trust that must be maintained for the sustainability of human life. These findings are relevant to contemporary environmental education and ecological ethics, which can contribute to raising environmental awareness in society. The petuah contained in this text emphasize not only the moral duty of humans toward nature, but also link spiritual piety with sustainable ecological action.